`f''(x)=8x^3+5`

`f'(x)=int(8x^3+5)dx`

`f'(x)=8(x^4/4)+5x+c_1`

`f'(x)=2x^4+5x+c_1`

Now let's find constant c_1 , given f'(1)=8

`f'(1)=8=2(1)^4+5(1)+c_1`

`8=2+5+c_1`

`c_1=1`

`:.f'(x)=2x^4+5x+1`

`f(x)=int(2x^4+5x+1)dx`

`f(x)=2(x^5/5)+5(x^2/2)+x+c_2`

Now let's find constant c_2 , given f(1)=0

`f(1)=0=2(1^5/5)+5(1^2/2)+1+c_2`

`0=2/5+5/2+1+c_2`

`c_2=-(2/5+5/2+1)=-(2*2+5*5+10)/10=-39/10`

`:.f(x)=(2x^5)/5+(5x^2)/2+x-39/10`

## Get

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

`f''(x)=8x^3+5`

`f'(x)=int(8x^3+5)dx`

`f'(x)=8(x^4/4)+5x+c_1`

`f'(x)=2x^4+5x+c_1`

Now let's find constant c_1 , given f'(1)=8

`f'(1)=8=2(1)^4+5(1)+c_1`

`8=2+5+c_1`

`c_1=1`

`:.f'(x)=2x^4+5x+1`

`f(x)=int(2x^4+5x+1)dx`

`f(x)=2(x^5/5)+5(x^2/2)+x+c_2`

Now let's find constant c_2 , given f(1)=0

`f(1)=0=2(1^5/5)+5(1^2/2)+1+c_2`

`0=2/5+5/2+1+c_2`

`c_2=-(2/5+5/2+1)=-(2*2+5*5+10)/10=-39/10`

`:.f(x)=(2x^5)/5+(5x^2)/2+x-39/10`